Benchmarking the Optimal Time Alignment of Tsunami Waveforms in Nonlinear Joint Inversions for the Mw 8.8 2010 Maule (Chile) Earthquake - Romano, F.; Lorito, S.; Lay, T.; Piatanesi, A.; Volpe, M.; Murphy, S.; Tonini, R. (Frontiers in Earth Science, 2020)
Finite-fault models for the 2010 Mw 8.8 Maule, Chile earthquake indicate bilateral rupture with large-slip patches located north and south of the epicenter. Previous studies also show that this event features significant slip in the shallow part of the megathrust, which is revealed through correction of the forward tsunami modeling scheme used in tsunami inversions. The presence of shallow slip is consistent with the coseismic seafloor deformation measured off the Maule region adjacent to the trench and confirms that tsunami observations are particularly important for constraining far-offshore slip. Here, we benchmark the method of Optimal Time Alignment (OTA) of the tsunami waveforms in the joint inversion of geodetic (GPS, InSAR, land-leveling) and tsunami (DART and tide-gauges) observations for this event. We test the application of OTA to the tsunami Green’s functions used in a previous inversion. We find that using just the first-order modeling correction introduced by OTA shifts the inferred slip distribution to a shallower position consistent with the slip models obtained by adopting more complex physics-based corrections. The retrieved model also predicts the observed seafloor deformation off the Maule region very well. Overall, this benchmarking of the OTA method can be considered successful. Furthermore, synthetic tests show that if the bias in the forward model is comprised only of delays in the tsunami signals, the OTA can correct them precisely, independently of the sensors (DART or coastal tide-gauges). When inverted to retrieve the slip for a real case, though, DARTs are shown to outperform tide-gauges. This gives an indication of the relative weights to be assigned when jointly inverting the two types of data.